Tender ironies, a tribute to Lothar Lutze - Chitre, Dilip; Sontheimer, Günther-Dietz; Brückner, Heidrun; Feldhaus, Anne (Manohar, 1994)
Festschrift for Lothar Lutze, German author and translator of Hindi and Bengali literature; comprises translations of poems, short stories from various Indian languages, and articles on Indological topics
Festschrift for Lothar Lutze, German author and translator of Hindi and Bengali literature; comprises translations of poems, short stories from various Indian languages, and articles on Indological topics
Keywords: Anthologie; Aufsatzsammlung; Hochschulschrift; Literatur; Indische Sprachen